INNOVATIVE HEALTH-FITNESS TECHNOLOGIES IN THE TRAINING OF YOUNG PANKRATIONISTS (Physical Culture and Sport: Scientific Perspective, 2025)
The article discusses the implementation of innovative health-fitness programs in the training of young pankrationists aimed at improving physical qualities, reducing injuries, enhancing functional state, and increasing psychological resilience. The purpose of the study is to theoretically and methodologically substantiate the use of innovative health-fitness technologies in the preparation of young pankrationists to improve their physical fitness, health level, and sports mastery. The training methods combine traditional principles with modern fitness technologies, allowing for high performance results. A key component is functional training, which includes exercises for developing coordination, strength, endurance, speed, and flexibility using body weight, elastic bands, kettlebells, and medicine balls. High-intensity interval training enhances aerobic and anaerobic endurance, explosive strength, which is important for pankration. The alternation of intense exercises and rest promotes the rapid achievement of optimal physical condition.Special attention is given to sports games during the off-season, which help maintain physical fitness, sustain motivation, and foster the development of special skills. These games improve coordination, speed, endurance, and reaction, as well as contribute to the improvement of tactical skills and the ability to make quick decisions. The off-season is a crucial recovery stage after intense competitions, and sports games contribute to the development of motor skills without the risk of injury.Active games with combat elements, such as maneuvering and control, help develop coordination, strength, and speed of reaction. Team games, particularly basketball and streetball, positively influence endurance, speed, and coordination, as well as shape social skills. Innovative health-fitness programs that incorporate various training methods are an essential element in the preparation of young pankrationists, ensuring the development of their physical, technical, and psychological qualities.
Keywords: pankration; fitness technologies; physical preparation; psychological preparation; young athletes